2013
DOI: 10.1587/transinf.e96.d.146
|View full text |Cite
|
Sign up to set email alerts
|

Round Addition Using Faults for Generalized Feistel Network

Abstract: SUMMARYThis article presents a differential fault analysis (DFA) technique using round addition for a generalized Feistel network (GFN) including CLEFIA and RC6. Here the term "round addition" means that the round operation executes twice using the same round key. The proposed DFA needs bypassing of an operation to count the number of rounds such as increment or decrement. To verify the feasibility of our proposal, we implement several operations, including increment and decrement, on a microcontroller and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…By the above result, in TWINE, the secret key can be derived because all round data at the final round are not whitened. This is similar to 128-bit CLEFIA [2].…”
Section: Round Addition Dfa On 80-bit Twinesupporting
confidence: 66%
See 2 more Smart Citations
“…By the above result, in TWINE, the secret key can be derived because all round data at the final round are not whitened. This is similar to 128-bit CLEFIA [2].…”
Section: Round Addition Dfa On 80-bit Twinesupporting
confidence: 66%
“…On the basis of this technique, we have shown that round addition DFA using a bypassing increment or decrement command is effective for attacks against cipher-implemented microcontrollers. Further, by supplying abnormal voltage, secret keys of DES and 128-bit CLEFIA can be derived using round addition DFA [2]. Recently, many lightweight block ciphers have been proposed for low-resource devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instruction skip is equivalent to replacing an instruction with a no operation in assembly language. Several researchers have investigated DFA using an instruction skip, or a bypass operation [29], [30], [31]. Instruction skip does not affect the registers, internal memory, and calculation process.…”
Section: Instruction Skipmentioning
confidence: 99%
“…Instruction skip does not affect the registers, internal memory, and calculation process. Successful instruction skip attacks have been reported for PIC16F877 [29], ATmega 128 [30], and ATmega 168 [31] microcontrollers. Choukri-Tunstall [29] and Park et al [30] showed that an entire Advanced Encryption Standard secret key could be reconstructed by skipping a branch instruction used to check the number of rounds.…”
Section: Instruction Skipmentioning
confidence: 99%